Dynamics of Self-Injury Behavior in Adolescents from a Broken Home Family - Evi Syafrida Nasution (Future Science, 2023)
Adolescence is a critical period of life with various biological, environmental, and social changes. When facing conflict, some teenagers choose to do self-injury to divert the pressure they are experiencing. The purpose of this study was to determine the dynamics of self-injury behavior of adolescents from broken-home families. The research methodology used in this study was a qualitative approach, the case study method. The data were collected by interview techniques and psychological tests. One subject was a teenage girl who had self-injured several times in the past year and came from a broken home. The data analysis technique used is thematic data analysis. The results of this study revealed that the subject's background self-injury was due to family problems and the environment. Parents separated (but not divorced). There was no parental role and break up with the boyfriend. This affects the formation of personality associated with self-injury behavior, namely introverted personality, difficulty communicating feelings, and low self-esteem. The subject self-injured by slashing his wrist and deliberately making his medical condition worse, just to divert the pressure he felt without any desire to kill himself, but this coping could not solve the problem and was only temporary. This study concluded that the subject self-injured because of family and environmental factors. Self-injury behavior in the form of cutting hands and making medical conditions worse was realized by the subject without any intention to commit suicide. However, this still could not solve the problem he was facing and only temporarily diverted the pressure he was feeling.